2015
DOI: 10.1002/chem.201504049
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of Trisubstituted Alkenes through Sequential Iron‐Catalyzed Reductive anti‐Carbozincation of Terminal Alkynes and Base‐Metal‐Catalyzed Negishi Cross‐Coupling

Abstract: The stereoselective synthesis of trisubstituted alkenes is challenging. Here, we show that an iron‐catalyzed anti‐selective carbozincation of terminal alkynes can be combined with a base‐metal‐catalyzed cross‐coupling to prepare trisubstituted alkenes in a one‐pot reaction and with high regio‐ and stereocontrol. Cu‐, Ni‐, and Co‐based catalytic systems are developed for the coupling of sp‐, sp2‐, and sp3‐hybridized carbon electrophiles, respectively. The method encompasses a large substrate scope, as various a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…Following our recent study on cobalt catalyzed carbozincation reactions, and in our long-term quest for the metal mediated functionalization of enamides, we disclose here a broadly applicable and original ynamide carbozincation. It is worth mentioning that carbometalation of alkynes, and, in particular, carbozincation, is one of the most important reactions due to the high functional group compatibility of organozinc reagents. Of particular interest is the cobalt-catalyzed carbometalation of alkynes, in view of the low cost and the low toxicity of cobalt.…”
mentioning
confidence: 99%
“…Following our recent study on cobalt catalyzed carbozincation reactions, and in our long-term quest for the metal mediated functionalization of enamides, we disclose here a broadly applicable and original ynamide carbozincation. It is worth mentioning that carbometalation of alkynes, and, in particular, carbozincation, is one of the most important reactions due to the high functional group compatibility of organozinc reagents. Of particular interest is the cobalt-catalyzed carbometalation of alkynes, in view of the low cost and the low toxicity of cobalt.…”
mentioning
confidence: 99%
“…[3,4] Despite requiring a stoichiometric amount of reductant or organometallic reagent, transition-metal-catalyzed "formal" hydroalkylation reaction between alkynes and alkyl halides, pseudohalides, or boranes is considered an appealing strategy in this field and has attracted great interest (Scheme 1 a). [5][6][7][8] Without using halides and other functional groups, C(sp 3 )ÀH bond alkenylation represents a promising method for conversion of alkynes to alkenes, and some elegant examples have been disclosed involving the direct C À H activation [9] and radical processes (Scheme 1 b). [10] Very recently, MacMillan and Rueping independently developed Ir and Ni dual-catalytic photoredox decarboxylative hydroalkylation reactions with carboxylic acids as the alkyl donors (Scheme 1 c).…”
mentioning
confidence: 99%
“…Our approach is based on Fe-catalyzed stereoselective addition of an alkyl radical, generated from an alkyl halide under reductive conditions, to ethynylboronic acid pinacol ester ( 1 , Figure b). The approach is built upon our previous work, which showed that an alkyl radical was generated through the reaction of an alkyl halide with an Fe­(I) species, produced by reduction of an Fe­(II) catalyst with Zn (Figure c,d). The alkyl radical could be trapped by a terminal aryl alkyne to form a vinyl radical stabilized by an aryl group.…”
mentioning
confidence: 99%